Association between sedentary recreational time and cardiac autonomic modulation in adolescent boys: cross-sectional study - Farah, Breno Quintella; Christofaro, Diego Giulliano Destro [UNESP]; Andrade-Lima, Aluísio; Saraiva, Bruna Thamyres Ciccotti [UNESP]; de Barros, Mauro Virgílio Gomes; do Prado, Wagner Luiz; Ritti-Dias, Raphael Mendes (Springer Nature, 2020)
Sedentary behavior has been shown to be an independent risk factor for high blood pressure, obesity, and low physical activity levels in adolescents. However, the association between sedentary recreational behaviors, such as TV viewing and using computer/video games, and cardiac autonomic modulation in adolescents is not well established. Therefore, the aim of this study was to investigate the association between the time spent on sedentary recreational activities and cardiac autonomic modulation in adolescents. This cross-sectional study included 1149 adolescent boys (aged 16.6 ± 1.2 years). Using a questionnaire, we evaluated their sedentary recreational activities and based on the time spent on these activities, the subjects were classified as high (> 2 h/day) or low (≤ 2 h/day) time spent in a sitting position. Heart rate variability (HRV) was used to assess cardiac autonomic modulation. Time (standard-deviation of all RR intervals [SDNN], root mean square of the squared differences between adjacent normal RR intervals [RMSSD], and the percentage of adjacent intervals over 50 ms [PNN50]), as well as the frequency domains (low [LF] and high [HF] frequency) of HRV were obtained. Longer time spent on sedentary recreational activities was found to be significantly associated with low RMSSD (OR = 1.42, 95% CI 1.11; 1.81) and PNN50 (OR = 1.47, 95% CI 1.15; 1.88). associations were maintained even after adjustments for time of day, abdominal obesity, high blood pressure, and physical activity levels. The time spent on sedentary recreational activities was not associated with SDNN (OR = 1.08, 95% CI 0.84; 1.38), HF (OR = 1.31, 95% CI 0.88; 1.94), LF (OR = 1.19, CI 0.94; 1.52), or LF/HF (OR = 1.19, 95% = 0.93; 1.51) (p > 0.05 for all). In conclusion, longer time spent on sedentary recreational activities is associated with poor cardiac autonomic modulation.
Keywords: Adolescents; Cardiovascular system; Heart rate; Sedentary behavior